Genotyping of Echinococcus granulosus Isolates from Human in Khorasan Province, North-Eastern Iran - BERENJI, Fariba (Iran J Parasitol, 2019)
BACKGROUND: Human hydatidosis is endemic in northeastern Iran. The present study aimed to investigate molecular diversity of Echinococcus granulosus isolates collected from human surgically. METHODS: Sixty human hydatid cysts (58 lung cysts and 2 liver cysts) were collected through surgery from Ghaem and Emam Reza hospitals in Mashhad University of Medical Sciences during 2015–2016. Cysts were characterized using polymerase chain reaction-restriction fragment length polymorphism (PCRRFLP) analysis of the internal transcribed spacer 1 (ITS1) gene and sequencing fragments of the genes coding for mitochondrial cytochrome c oxidase subunit 1 (cox1) and NADH dehydrogenase subunit I (nad1). RESULTS: Overall, 55 out of 60 Echinococcus granulosus cysts (91.6%) were determined as the G1 strain, 4 cases (6.6%) were determined as the G6 strain and 1 sample was not identified. CONCLUSION: Although sheep strain (G1) is dominated in human patients in Great Khorasan, the prevention of camel-dog cycle should pay attention in this region.